2001
DOI: 10.1046/j.0956-540x.2001.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of successive pTRMs carried by pyrrhotite in Himalayan metacarbonates: an example from Hidden Valley, Central Nepal

Abstract: Summary Low‐grade metacarbonates from the Tethyan Himalaya were sampled for palaeomagnetic studies in Hidden Valley (Central Nepal). The remanence is carried by pyrrhotite, evidenced by thermomagnetic runs of susceptibility (Hopkinson peak at ∼300 °C), alternating field demagnetization, isothermal remanent magnetization acquisition and subsequent thermal demagnetization. The palaeomagnetic directions reflect a Tertiary overprint after the main folding event, probably synchronous with the metamorphism. Normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Besides the widespread secondary remanence residing in pyrrhotite [e.g., Crouzet et al ., ; Appel et al ., ], we have detected pervasive remagnetization residing in authigenic magnetite in unmetamorphosed carbonate rocks of the TH. Paleogeographic reconstructions of the Tibetan Himalaya and India‐Asia collision could be seriously flawed when remagnetization of carbonate rocks is not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the widespread secondary remanence residing in pyrrhotite [e.g., Crouzet et al ., ; Appel et al ., ], we have detected pervasive remagnetization residing in authigenic magnetite in unmetamorphosed carbonate rocks of the TH. Paleogeographic reconstructions of the Tibetan Himalaya and India‐Asia collision could be seriously flawed when remagnetization of carbonate rocks is not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the 150% thickening associated to D2 could explain the observed temperature. Whatever, palaeomagnetic investigations performed in the Dolpo-Manang area (Appel et al, 1991;Crouzet et al, 2001aCrouzet et al, , 2003Schill et al, 2003) have evidenced a post-deformation remanence acquisition carried by pyrrhotite. This remanence is acquired during the cooling just below 320°C (Rochette, 1987;Dunlop et al, 2000).…”
Section: Consequencesmentioning
confidence: 95%
“…For the other areas, the existence of a major thrust carrying material over the studied areas can be assumed. The existence of such a thrust was proposed by Guillot (1993) and Guillot et al (1995) in order to justify the barometric results in the contact aureole of the Manaslu granite and more recently by Crouzet et al (2001a) in order to explain paleotemperatures higher than 325°C in Triassic metasediments of the Hidden Valley area deduced from palaeomagnetic investigations. Except the Nar Tö thrust, carrying the Ratna nappe over the Triassic of the TH in Himlung Himal area Guillot, 1998, 1999), no other geological surveys have ever evidenced such a thrust in northern Nepal.…”
Section: Consequencesmentioning
confidence: 95%
See 1 more Smart Citation
“…Pyrrhotite has been used as an index mineral in metamorphic belts to delineate isograds (Crouzet et al, 2001;Horng et al, 2012). Crouzet et al (2001) reported a pyrrhotite-held postmetamorphic partial thermoremanent magnetization in metamorphic rocks acquired during postorogenic uplift.…”
Section: Pyrrhotite As An Indicator Of Variable Thermochemical Activitymentioning
confidence: 99%